The Narratives of Hate Used by Romanian Parties Labelled as Far-Right: A Comparative Narrative Analysis - Dragomir, Susana (Journal for the study of religions and ideologies, 2023)
This article presents a qualitative comparative analysis of the primary hate narratives employed by three political parties: the Iron Guard Party propaganda, the Greater Romania Party (PRM), and the Alliance for the Union of Romanians (AUR). The study focuses on the following variables: ‘foreigners,’ ‘freemasons,’ ‘Jews,’ ‘protection of Faith and Nation,’ and ‘rotten political elites.’ The analysis is based on official propaganda materials of each party, including patriotic songs, leaflets, newspapers, programmatic documents, and speeches of the leader for the Iron Guard. In the case of the PRM, the analysis includes the party’s official program, ideology, poems, and pamphlets by the leader (Corneliu Vadim Tudor), speeches, interviews, press articles, and extracts from party journals Romania Mare (Greater Romania) and Tricolorul. The AUR’s official website, political program and ideology, Facebook posts, pages, press interviews, articles, and speeches of its leaders constitute the object of analysis. The narratives extracted were analyzed using the ATLAS.ti software, revealing striking resemblances among the hate narratives employed by the parties.